Youth in the Netherlands Study (JOiN): study design - Huizink Anja C; Greaves-Lord Kirstin; Evans Brittany E; Euser Anja S; van der Ende Jan; Verhulst Frank C; Franken Ingmar HA (BMC, 2012)
Abstract Background Adolescence is a critical developmental period regarding exposure to substances. Therefore, it is important to be able to identify those adolescents who are most vulnerable to substance abuse in the (near) future. The JOiN study was specifically designed to examine two endophenotypes of adolescent substance use in a normal risk (NR) and high risk (HR) sample of adolescents: (1) behavioural disinhibition, and (2) individual differences in stress sensitivity. Methods The NR adolescents were part of a longitudinal general population study at the Erasmus Medical Center in Rotterdam, the Netherlands of children and adolescents initially aged 6 to 18 years old. Three assessment waves have been nearly completed, and data are available of N = 711 participants for stress sensitivity measures, and of a subsample of N = 110 for electroencephalography (EEG) measures. Added to this study, HR adolescents who had at least one parent with a substance use disorder and who were treated by an outpatient clinic of a primary addiction care provider were approached via their parent(s). In total, N = 83 adolescents formed this HR sample. NR and HR adolescents participated in standardized stress procedure and EEG procedures in our laboratory. Questionnaires were filled out on background variables, behavioural and emotional problems, and substance use, and a diagnostic interview was conducted with adolescents and parents to assess psychopathology symptoms. DNA was collected through saliva or blood samples. Discussion The design of the JOiN study is optimal for examining the predictive role of endophenotypes of adolescent substance use. The combination of different methods, i.e. stress physiology, electrophysiology, genetics, and questionnaire data from several informants on a range of behaviours and environmental factors enables the investigation of the multifactorial nature of adolescent substance use.